A Methods engineering study on Siegranz Chem Works Laboratories - Buenviaje, Arlene; Concepcion, Tatiana Joy; Diaz, David John; Navarro, Julie Anne (College of Engineering, 2002)
SiegRanz Chem Works (SCW) Laboratories is a medium-scale manufacturing system that produces both branded and generic household products, which are sold all over the Philippines. This Methods Engineering study aims to increase the productivity and efficiency of the production processes of SCW Philippines, Inc. and increase the profits of the organization through the use of concepts and techniques learned in IE 32 : Methods Engineering. Using a Streamline Diagnose Diagram (Fig. 3.1), the group was able to identify some of the most pressing factors that led to problem in productivity and efficiency of the company. These factors included the inability of the plodder to extrude 100 percent of the laundry bar mixture, improper storage and mishandling of the finished products, which led to a large number of rejects is generated and an unstrategic location of the packing materials, which led to delays in the production process. Through creative and logical generation of alternatives, some solutions to these problems were formulated. Some solutions to the inability of the plodder to extract 100 percent of the laundry bar mixture were to find ways for better production scheduling and to buy new plodders. Through better scheduling, the company would have a 20.02 percent increase in production, which translated to an additional P117,936.00 in annual profit. Purchasing new plodders would result in an additional P114,168.55 or a 46.51 percent increase in profit. Solutions formulated for the mishandling of finished products were the establishment of standard operating procedures (SOPs) for the packing, stacking and handling of boxes, and to hire a supervisor to implement these SOPs. Though the hiring of a supervisor would cost the company P10,000 monthly, the implementation of these SOPs would still give the company an additional monthly profit of P6,936.62. The problem of an unstrategic location of packing materials could easily be solved by redesigning the layout of the plant without having to renovate, a step that would reduce delays in production. Implementation of these alternatives would mean an increase in the system's productivity and efficiency. This would translate to an increase in profits and ultimately, an increase in return on investment.